A Pilot Study Embedding Clinical Pharmacists Within an Interprofessional Nephrology Clinic for the Initiation and Monitoring of Empagliflozin in Diabetic Kidney Disease. (June 2021) - Triantafylidis, Laura K.; Hawley, Chelsea E.; Fagbote, Christopher; Li, Jiahua; Genovese, Nicole; Paik, Julie M.
Background: The American Diabetes Association (ADA) recommends sodium-glucose cotransporter-2 (SGLT2) inhibitors as the second medication to be started, after metformin, for patients with chronic kidney disease (CKD). Sodium-glucose cotransporter-2 inhibitors may cause volume, blood pressure, and electrolyte disturbances; consequently, frequent monitoring and adjustments to other diabetes, blood pressure, and/or diuretic medications may be necessary. Objective: To evaluate the safety and efficacy of an interprofessional clinic model partnering nephrologists and pharmacists for the initiation and monitoring of SGLT2 inhibitors. Methods: A clinical pharmacist was embedded within the nephrology clinic to provide patient education, telephone follow-up, and to work collaboratively with the nephrologists. Diabetes, hypertension, and diuretic regimens were adjusted as needed after empagliflozin initiation. Diabetes regimens were adjusted to adhere to the 2019 ADA guidelines that promote agents with CKD and atherosclerotic cardiovascular disease benefit. Results: Fourteen patients were initiated on empagliflozin during the study period. Urine albumin-to-creatinine ratio (UACR) improved (mean % change −12% ± 61%); the mean percentage change was greater in patients with a higher baseline UACR. The mean change in hemoglobin A1c was 0.3% ± 0.6%. Common adverse reactions were observed and improved over time; no serious adverse drug reactions occurred. Finally, empagliflozin initiation necessitated adjustments to diabetes, hypertension, and diuretic regimens in almost all patients (n = 13, 93%). Conclusion: The implementation of an innovative, interprofessional care model within a nephrology clinic for the initiation and monitoring of empagliflozin in patients with DKD demonstrated clinical benefit with minimal safety concerns.